ADJUSTABLE-HEIGHT SPRAY NOZZLE SYSTEM FOR AIRBORNE AGRICULTURAL SPRAYING - MOHAMED FAUZI, FAHIMA FARHA (IRC, 2019)
The application of crop production and protection is the crucial part in every agricultural development in order to produce a good quality of products in a large quantity. In order to achieve a decent quality of spraying process, the unmanned aerial vehicle (UAV) or an autogyro is used. UAVs and gyroplane are an aircraft that is used to spray the pesticide, fertilizers in the crop field. However, due to the uncertainty of using the aircrafts, there should be an improvement in order to have a tremendous term in producing the product. This project shall study and test the system development of spray system where the spray nozzle that is mounted on the wing of the aircrafts can be adjusted and varied by following the input that have been collected such as the altitude, speed and also the GPS accordingly.